A systematic review of the morphology and function of the sacrotuberous ligament. Issue 3 (5th February 2019) - Aldabe, Daniela; Hammer, Niels; Flack, Natasha A.M.S.; Woodley, Stephanie J.
Abstract : The sacrotuberous ligament (STL) has been linked to conditions such as pelvic girdle pain and pudendal nerve entrapment, yet its contribution to pelvic stability is debated. The purpose of this review was to explore the current understanding of the STL and highlight any gaps in knowledge regarding its anatomy and function. A systematic search of the literature was conducted, focussing on the morphology and attachments of the STL, the relationship of the STL with surrounding structures, and its neurovascular supply and function. A total of 67 papers and four textbooks were obtained. The attachment sites of the STL are largely consistent; however, the extent of its connections with the long head of biceps femoris, gluteus maximus, piriformis, the posterior layer of the thoracolumbar fascia, and sacrospinous ligament are unclear. Morphometric parameters, such as mean STL length (6.4–9.4 cm), depth (0.3–0.4 cm), and width (1.8–3.5 cm, at its mid‐point) are variable within and between studies, and little is known about potential side‐, age‐, or sex‐related differences. The STL is pierced in several sites by the inferior and superior gluteal arteries, but information on its innervation pattern is sparse. Functionally, the STL may limit sacral nutation but it appears to have a limited contribution to pelvic stability. Some morphological aspects of the STL warrant further investigation, particularly its connections with surrounding structures, innervation pattern and function. Knowledge of the detailed anatomy and function of this ligament is important to better understanding its role in clinical conditions. Clin. Anat. 32:396–407, 2019. © 2018 Wiley Periodicals, Inc.